Group Resilience: The Place and Meaning of Relational Pauses. Issue 9 (September 2019) - Barton, Michelle A.; Kahn, William A.
Recent scholarship on resilience has shed light on the processes by which organizations absorb strain and maintain functioning in the face of adversity. These theories, however, often focus on the operational impacts of adversity without accounting for the strain it puts on organizational members and their abilities to work effectively together. We apply a relational lens to better understand how adversity, and the anxiety it triggers in people, affects processes of organizational resilience. This conceptual frame enables us to begin uncovering the relational micro-dynamics underlying the absorption of strain. Drawing on group relations theory, we describe two trajectories of intragroup behavior in which strain, in the form of adversity-triggered anxiety, is either acted out or defused. In the brittle trajectory, group members react to anxiety with defensive patterns that leave them vulnerable to effects of adversity. In the resilience trajectory, groups defuse and mitigate adversity-triggered anxiety through a reflective process we call "a relational pause, " ultimately leaving them strengthened and resilient. We elaborate the model by exploring the potential fragility of relational pauses and likely factors that influence groups' ability and tendency to enact resilience.